Zum Gedenken an Peter Herrmann. 22. 5. 1927 - 22. 11. 2002 - Seminar für Alte Geschichte (Hamburger Universitätsreden Neue Folge, 2004)
This volume documents the speeches given at the academic commemoration ceremony for Peter Herrmann at the Warburg-Haus in Hamburg on May 15, 2003.